EFFECTIVENESS OF COMBINED RESISTANCE EXERCISE AND WARMWATER IMMERSION ON FOOT SENSITIVITY IN TYPE 2 DIABETESMELLITUS: A PRE-EXPERIMENTAL STUDY - Arum Dwi Ningsih (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia. One complication in DM patients is diabetic ulcers that begin with peripheral neuropathy. This peripheral neuropathy causes decreased sensitivity in the feet, so that people with diabetes mellitus often experience loss of sensation in the feet. The purpose of this study was to determine the effect of a combination of resistance exercise and warm water soaks on the sensitivity value of the feet of diabetes mellitus patients. The research method used was quantitative with a Pre-Experimental design, namely One Group Pretest-Posttest design. The population of this study were all type II Diabetes Mellitus patients under the management of the Blooto Health Center Work Area, Mojokerto City. The sampling technique used was purposive sampling with a sample size of 32 respondents. The results of the statistical test with the Wilcoxon Rank Test showed a p value = 0.001 (p <0.05), indicating that there was a significant difference between before and after the intervention. The z value = -5.099 also strengthens the existence of significant changes with the direction of change indicating improvement.